Alternative Paths, Phrase Expansion, and the Music of Felix Mendelssohn. (3rd June 2019) - Jarvis, Brian Edward; Peterson, John
Abstract: William Rothstein's seminal work on phrase rhythm has been foundational for scholars who study phrase expansion using Schenkerian principles, such as David Beach, Charles Burkhart, Joseph Kraus, and Samuel Ng. Other scholars consider phrase expansion from the perspective of William Caplin's form-functional theory, such as Janet Schmalfeldt and Steven Vande Moortele. Both groups tend to emphasize structural concerns. Recent theories of musical meaning, however, challenge analysts to consider phrase expansions through an expressive lens. This article engages with that challenge using the metaphor of musical motion, a concept that is informally present in numerous analytical writings but was formalized in work on conceptual metaphors by Steve Larson and Mark Johnson. In particular, we introduce a category of expansion techniques called "alternative paths" in which a phrase deviates from its expected course toward a goal via the addition of new material. By defining how the new material is initiated and concluded, alternative paths provide a more nuanced view of passages that might otherwise be described by the more generic terms "parenthesis, " "interpolation, " or "purple patch." We use Felix Mendelssohn's works to demonstrate the effectiveness and flexibility of our approach, though the theory of alternative paths is by no means limited to that repertoire.